Analisis Kesalahan Hasil Terjemahan Mesin Penerjemah Teks Bahasa Jerman ke dalam Bahasa Indonesia - Sudarmaji Sudarmaji; Iman Santoso; Retna Endah Sri Mulyati (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
Many online translation machines can translate more than 100 languages, including German into Indonesian and vice versa. However, the accuracy and standardization of the results still need to be investigated. This study aims to identify language errors in the translation of German texts into Indonesian using Google Translate and Bing Translator. This research is a descriptive qualitative research based on language error analysis. The data is derived from 12 German news articles published by Deutsche Welle. These German texts were translated into Indonesian using these two machine translators. The translated texts were analyzed for language errors at the semantic, morphological, and syntactic levels. The results of this study show that there are still language errors at the semantic, morphological, and syntactic levels in the translated texts produced by Google Translate and Bing Translator. Both translation machines tend to translate the text word for word. A translation result is an initial form of translation that needs to be edited to obtain an accurate translation.